Policy Guidelines for Records Management in Nigerian University Libraries - Mohammed Mairiga CLN, Innocent Sunday Idakwo CLN & Usman Mohammed Song CLN, Jacob Olanrewaju Ojo CLN, Hussaini (COVENANT JOURNAL OF LIBRARY AND INFORMATION SCIENCE, 2019)
This study was conducted to examine the policy guidelines for records management in Nigerian university libraries with a case study of libraries of federal universities in North Western States of Nigeria. The study aimed to identify the impact of policy guidelines on staff records management practices towards effective information resource management, the policies guiding the management of staff records and the challenges in the management of staff records of the libraries under study. The study population included seven staff records officers in the libraries studied. Face-to-face interview was the main instrument for data collection with the aid of semi-structured interview schedules with accompanying checklist. Data collected were analyzed using thematic analysis. The study found out that policy guideline in records management in the libraries under study has a positive impact on effective information management. It also revealed that there are policies guiding the management of records which partly included that records are only to be handled by designated officers, records are not to be destroyed, rather, they are to be kept in the archives, and there should be separation of non-current records from current records. However, these policies are not written or documented. However, they can be regarded as policies as they affect the ways and manner these records are handled. The libraries are faced with the challenges of poor policy guidelines, inadequate funding, inadequate accommodation, poor electricity supply, and low morale of staff, lack of training and retraining of staff, and lack of strong support from the top managerial staff. Staff training and re-training, recruitment of staff to be done on merit, good attitude to work by staff, legislation and adequate funding among others are the recommendations.